Visual Research Methods: Recognising the Social Identities and Behaviour of Non-Smokers and Smokers - Kirsi Purhonen; Marja-Leena Kauronen; Olli Lehtonen; Angelika Polak; Valdemar Kallunki (Ekonometria)
This article presents the visual research methods (VRM), a procedure containing an iterative circle for detecting smokers and non-smokers among adolescents and young adults. Qualitative and quantitative approaches were used to develop the theoretical framework and questionnaires, conduct workshops, content analysis and statistical modelling, and to examine and interpret the results. The visual context that detects smokers and non-smokers concerns the social norms and environment, attitudes, beliefs, role models, individual factors, situational context and healthy vs. unhealthy lifestyle. VRM provide precise results regarding the phenomenon and offer a sympathetic, considerate and suitable way to examine it. The interpretations of the visual context of smoking generates valuable information for smoking prevention methods compared with the traditional verbal questionnaire.(original abstract)